Analisis Manfaat Implementasi Penerapan Kegiatan Kewirausahaan Bazar terhadap Perkembangan Life Skill Siswa di UPTD SDN Mlajah 2 - Annisak, Elvy Risky; Jannah, Ana Naimatul; Koesmini, Astien Diena (Edu Berkah Khatulistiwa, 2024)
This research aims to analyze the benefits of holding Bazaar Entrepreneurship Activities at UPTD SDN Mlajah 2. The location of this research is at SDN Mlajah 2, Bangkalan. The method used in this research is a qualitative descriptive method with data collection techniques in the form of observation and interviews. The subjects in this research were one of the Class VI A students, one of the Class VI B students, and one of the Teaching Assistant students. The results obtained in this research are that there are many benefits that students obtain from implementing Bazaar entrepreneurial activities at UPTD SDN Mlajah 2, namely: Can increase creativity and innovation possessed by students, can increase student responsibility, can increase the attitude of mutual cooperation between each group , can increase students' independent attitudes, and can increase students' self-confident attitudes. The practical implication that needs to be made is that there is continued support from the school so that students are able to develop an entrepreneurial spirit which will later be useful and provide provisions for students for their future.